Performance, Award, Institutional Ownership, Media Coverage: Dampak Terhadap Environmental Disclosure di Indonesia - Adita Mutiara Annisa (2022)
This study aims to examine how environmental performance, environmental award, institutional ownership, and media coverage influence environmental disclosure. The population in this study were non-financial companies listed on the Indonesia Stock Exchange and PROPER for the period 2018 - 2020. The research sample was determined using purposive sampling. This study has a sample of 83 data processed using the IBM SPSS 26 statistical program and analyzed using multiple regression. The result of the statistical tests proved that institutional ownership has a positive effect on environmental disclosure. Meanwhile, environmental performance, environmental awards, and media coverage do not affect environmental disclosure.